Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016 IEEE 32nd International Conference on Data Engineering (ICDE) 2016
DOI: 10.1109/icde.2016.7498256
|View full text |Cite
|
Sign up to set email alerts
|

An embedding approach to anomaly detection

Abstract: Network anomaly detection has become very popular in recent years because of the importance of discovering key regions of structural inconsistency in the network. In addition to application-specific information carried by anomalies, the presence of such structural inconsistency is often an impediment to the effective application of data mining algorithms such as community detection and classification. In this paper, we study the problem of detecting structurally inconsistent nodes that connect to a number of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 29 publications
(56 reference statements)
0
48
0
Order By: Relevance
“…Figure 13: The anomalous (red) nodes in embedding, and A, B, C, D are four communities (Hu et al 2016). Image extracted from (Hu et al 2016). function φ parameterized by θ so as to bridge these two representations.…”
Section: Network Alignmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 13: The anomalous (red) nodes in embedding, and A, B, C, D are four communities (Hu et al 2016). Image extracted from (Hu et al 2016). function φ parameterized by θ so as to bridge these two representations.…”
Section: Network Alignmentmentioning
confidence: 99%
“…Advanced information preserving network embedding Methods Source code Information diffusion (Bourigault et al 2014) https://github.com/ludc/social_network_diffusion_embeddings Cascade prediction https://github.com/chengli-um/DeepCas Anomaly detection (Hu et al 2016) https://github.com/hurenjun/EmbeddingAnomalyDetection Collaboration prediction (Chen and Sun 2017) https://github.com/chentingpc/GuidedHeteEmbedding direction is to explore the possibility of designing network embedding for more specific applications. For example, whether network embedding is a new way to detect rumors in social network (Seo, Mohapatra, and Abdelzaher 2012;Zhang et al 2015)?…”
Section: More Advanced Information and Tasksmentioning
confidence: 99%
“…It was found that ego-networks with an equal number of nodes and edges is a network with a star-structure, were found to deviate from the derived power law [1]. Others attempted to improve the identification of nodes with star or clique structure by introducing alternate local features of the ego-network [9,14], incorporating features from the extended neighborhoods into the model [9,12], or by identifying so-called hubs, nodes that do not share a certain fraction of common neighbors with any of their adjacent nodes [24]. It should be noted that the node anomaly is considerably different from merely selecting high betweenness centrality nodes in the network, because this centrality measure does not differentiate between edges in or between different parts of the network, while node anomalies typically do [12].…”
Section: Related Workmentioning
confidence: 99%
“…More recent work in this area looks into the attributed network by incorporating the vertex attributes [28,21,17]. Only a couple of recent works attempted to discover network outliers using network embeddings [6,11]. These efforts, however, do not apply to attributed networks.…”
mentioning
confidence: 99%